Does Training Matter? Evidence from Performance Management Reforms. (3rd February 2015) - Kroll, Alexander; Moynihan, Donald P.
Abstract: Training is much discussed but rarely studied in public management. Using multiple waves of survey data, the authors examine the effects of training on the implementation of performance management reforms in the U.S. federal government, asking whether those exposed to training are more likely to use performance data and strategic goals when making decisions. Training is positively associated with reform implementation, but there is little evidence that this association can be explained by the development of specific capacities to overcome performance management challenges. The findings offer two implications for the practice and study of training. The authors propose that training is likely to succeed if it is designed and funded to close specific capacity gaps needed for successful reform implementation. However, it is also necessary to better understand alternative causal mechanisms by which training facilitates reform implementation, such as explaining and justifying reforms. Practitioner Points Training can facilitate the implementation of new policies by providing information about the policies, justifying why they are needed, and giving employees the capacity to put the new policies in place. Using training to build specific employee capacities is more complex, resource intensive, and rare than using training to provide information and justify reforms. Effective training in government requires not just more resources but also better understanding of the specific capacities needed and how to create them—research can help by identifying the most significant capacity gaps in policy implementation.